Mos only and mos-c circuit design - Kızılırmak, Şafak Murat (My University, 2019)
MOS-ONLY AND MOS-C CIRCUIT DESIGN Active filters have taken a considerable attention as a necessary building block of analog circuit design. There are many applications that need filters such as radio communication, audio electronics, biomedical applications, Very Large Scale Integrated circuits, etc. In design of active filters, passive elements like resistors and capacitors are also used with active elements like opamps, current conveyors, and OTAs, etc. These passive elements cause some limitations and they determine the quality of filters from many perspectives. Biomedical signal processing circuits need filters with very low cut-off frequencies. In order to obtain such small frequency range, the designer has to adjust the capacitance and resistance values. The only way to obtain a very small cut-off frequency is to use large valued capacitance or resistance values. This means an increase in the layout area, price, noise values, and power consumption, etc. Filter circuits, that exploit the intrinsic capacitors, Cgs and Cgd, and also the transconductance, gm, of the MOS transistor, instead of external passive circuit components such as resistors, capacitors or inductors, have received considerable attention in the last decade. It is clear that these circuits serve some important advantages some of which are: low chip area, high frequency of operation, low power consumption, low noise values, etc. Until now, a considerable amount of MOS-Only and MOS-C active filters suggested. In the thesis, the first step is to give and argue the opamp based active filters. Then the proposed MOS-Only filters are introduced.

SADECE MOS VE MOS-C DEVRE TASARIMI Analog devre tasarımında aktif filtreler kullanılması gerekli bloklar olarak dikkat çekmektedir. Radyo haberleşme, audio elektronik, biyomedikal elektronik, VLSI Sistemler gibi birçok uygulama alanında filtrelemeye ve filter devrelerine ihtiyaç duyulur. Aktif filtrelerde direnç, kapasite gibi pasif elemanların yanında OPAMP, akım taşıyıcılar ve OTA gibi aktif elemanlarda kullanılır. Filtre devrelerinde kullanınlan bu pasif elemanlar filternin kalitesini belirlemede birçok sınırlamalara neden olurlar. Bütün bunların yanında özellikle biyomedikal uygulamalarda çok düşük frekans aralıklarında çalışmak gerekmektedir. Bu düşük sinyal aralığını yakalamak için tasarımcı pasif elemanların değerleri ile oynamak zorundadır. Pasif filtrelerde düşük frekans aralığı elde etmek için yüksek değerlerde kapasite ve dirençler kullanmak gerekmektedir. Bütün bu ayarlamalar çip alanine, maliyeti ve güç tüketimini arttırmaktadır. Son yıllarda, pasif direnç ve kapasitelerin yerine MOSFET’in iç kapasite değerleri olan Cgs, Cgd ve aynı zamanda transkondüktans gm ‘i kullanarak filter devresini kurmak büyük önem kazanmıştır. Bu şekilde kurulan filter devreleri daha az çip alanı kaplamaları, az güç tüketmeleri gibi avantajlara sahiptirler. Bugüne kadar çeşitli MOS-Only ve MOS-C aktif filtreleri önerilmiştir. Bu tezde de OPAMP bazlı aktif filtrelerden başlanacak ve sonrasında önerilen MOS-Only devreler sunulacaktır. MOS ONLY AND MOS-C CIRCUIT DESIGN
Keywords: Electrical engineering; Electronics; Elektrik mühendisliği; Elektronik; Engineering; MOS ONLY AND MOS-C CIRCUIT DESIGN MOS ONLY AND MOS-C CIRCUIT DESIGN; Mühendislik